PENINGKATAN MUTU PENELITIAN DI INDONESIA DALAM MENGATASI MASALAH PENDIDIKAN - Saleh Hidayat (Program Studi Pendidikan Biologi Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2018)
PISA 2003, 2006,2009, 2012, and 2015 results show that Indonesian students’ ability for reading, science, and mathematic aspect are still in ten lowest ability countries. However, data reality in field show the research amount especially in education scope are very large. The existence of a gap between research potential that can be produced by survey results of PISA 2013—2017 bring up the statements 1) what causes the implementation of Indonesia research does not have significant impact on increasing Indonesia’s ranking in PISA? and 2) how the efforts that can be done in improving Indonesia research quality? The study result indicates that there are three main factors causing research quality in Indonesia are still low 1) the obstacles at government policy level; 2) subtract the researchers with doctoral qualification, and 3) the low growth potential of research atmosphere in Indonesia. Efforts that can be done 1) create conducive policy for researchers; 2) add the acceptance quota for doctor’s scholarship under 40 years old; 3) add of quota’s budget for research, and 4) downstream the research results to the teachers in improving the learning process. Conclusions on Indonesia research quality have been a lot, but need a good management by downstream the research mapping to the obvious community.